"Migration Is Not a Crime": Migrant Justice and the Creative Uses of Paddington Bear. Issue 3 (22nd March 2022) - Seitz, David K.
Abstract : Created in 1957, the well-known English children's book character Paddington Bear is the product of a dizzying number of displacements. Author Michael Bond (1926–2017) was inspired to make Paddington an undocumented migrant by World War II and Cold War mass evacuations in Europe, but he transposed Paddington's origins to the troped space of "Darkest Africa" only to relocate them to "Darkest Peru." Fleeing earthquake for England, Bond's ursine protagonist assumes the name of the London train station where he is "found." The story's literary and film critics have challenged its elevation to universality, arguing that it extends colonial discourse and idealizes Paddington as a nonthreatening, assimilated migrant. This article complicates those claims by tracing the character's emergence as an icon of migrant justice movements in the United Kingdom and Europe, turning to object relations psychoanalysis to examine Paddington's complex affective pull. Drawing on archival work in Bond's papers and interviews with his contacts, including migrant justice activists, I contend that although Paddington's literary construction reflects imperial imaginaries, his reception also attests to the transformative, solidaristic, and creative uses of cultural objects.